L’estetica di Romano Guardini (II): Gli sviluppi dei primi anni Venti. Verso una comprensione matura dell’arte - Ascencio LC, Juan G. (Alpha Omega, 2012)
This article – the second of a series – studies the developments that took place in Romano Guardini’s aesthetic thought from 1920 up to 1925. Without departing completely from the liturgical insights of the late 1910’s, Guardini moves towards a more concrete and reflexively mature approach, thanks to theories about polarity and “encounter”, and his ongoing dialogue with phenomenology. He now places the work of art, and not beauty, at the center.